Fracture characterization of pristine/post-consumer HDPE blends using the essential work of fracture (EWF) concept and extended finite element method (XFEM). (May 2015) - Na, Sukjoon; Spatari, Sabrina; Hsuan, Yick G.
Highlights: Adding recycled HDPE transfers the failure mode from ductile to brittle. 3-D XFEM can simulate the EWF test, particularly for brittle failure region. Increasing recycled HDPE linearly decreases the plane-strain specific EWF. Increasing recycled HDPE nonlinearly decreases the plane-strain specific non EWF. Abstract: The effect of recycled HDPE on plane-strain fracture properties of pristine HDPE was studied using the essential work of fracture concept. The plane-strain specific EWF decreased linearly as recycled content increased while the plane-strain specific non-EWF exponentially decreased. The specific non-EWF was investigated using the extended finite element method. The nonlinearity of specific non-EWF was influenced by the shape factor ( β D ) and the specific non-essential fracture work per unit volume ( w p, D ), both of which were non-linearly related to recycled content. Blending brittle recycled material to ductile pristine HDPE decreased the fracture toughness and the crack growth resistance.